Agama Rakyat Di Jawa: Melacak Akar Sosio-Historis Toleransi-Sinkretis - Sumbulah, Umi (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2006)
The author discusses about Islam in Java, that has a very unique character in terms of religious rites and expression. At the very beginning, the spread of Islam adopted the process of acculturation with local cultures. The acculturation is not just an expression of heterogenuous Javanese culture, but very much supported by political power. Mataram Islamic Kingdom had played a very crucial role in combining Islamic belief with the local culture that was very much influenced by Budhism and Hinduism. The author also highlights the deterioration of Islamic elites and grass-roots because of the presence of colonialism in 19th century. However, the notion of acculturation remains intact and serves as a form of religious tolerance character among Javenese Moslems.